If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -2 = 8x + 5 Reorder the terms: -2 + 12x = 8x + 5 Reorder the terms: -2 + 12x = 5 + 8x Solving -2 + 12x = 5 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -2 + 12x + -8x = 5 + 8x + -8x Combine like terms: 12x + -8x = 4x -2 + 4x = 5 + 8x + -8x Combine like terms: 8x + -8x = 0 -2 + 4x = 5 + 0 -2 + 4x = 5 Add '2' to each side of the equation. -2 + 2 + 4x = 5 + 2 Combine like terms: -2 + 2 = 0 0 + 4x = 5 + 2 4x = 5 + 2 Combine like terms: 5 + 2 = 7 4x = 7 Divide each side by '4'. x = 1.75 Simplifying x = 1.75
| 16x^2-10000x+90000=0 | | 2t-8-1t=-3 | | 16x+4y=152 | | 21m-49m= | | -x^2-4x+21=0 | | b^2n-c^8n= | | -12xy^3z^2-28y^3z-20x^2y^2z^2= | | 2a+7d=5d+15 | | 25x^2-24x-9=7x+12x-18 | | 12x^2-94x-70=0 | | a^5-3a^4+a^3= | | 2(1x+2)=1(2+3x) | | 3x-4x+1=-2x+5+5x | | x+2=-x-3 | | 5x+2+2x-7=7 | | 12x^2-92x-68=0 | | 3.7w=11.1 | | 7x+146= | | 18x+2=99-21-28x | | 8(1-y)-3(y+2)=2(y+1) | | 3x-6y+10=0 | | 7x-9-11-x=12 | | 8(1-x)-3(2-2x)=2(x+1) | | 5y+27+4y=9 | | 57-5x=4x+23 | | 4x(x-7)+13=27 | | 8-7x=31-4x | | 8.7=d+8.7 | | 5x-(2x+3)=4x-30 | | 4(7x+7)-5=28x+23 | | y=11x^2-90x-68 | | 15x+6y=0 |